Novel (NH4)4[NiMo6O24H6]·5H2O – TiO2 composite system: Photooxidation of toluene under UV and sunlight-type illumination - Muñoz Batista, Mario J. (2018)
A series of composite materials based on titania and growing quantities of the (NH4)4[NiMo6O24H6]·5H2O heteropolyacid (NiMo6 HPA) was tested in the gas-phase toluene photo-oxidation reaction. Materials were characterized with the help of chemical analysis, X-ray diffraction, porosimetry, electron transmission and scanning microscopies, as well as X-ray photoelectron and UV–visible diffuse-reflectance spectroscopies. Photoactivity performance was assessed under UV and sunlight-type illumination conditions through the calculation of the true quantum efficiency to measure activity as well as the analysis of the selectivity of the reaction. The composite system having a 3 wt. % of the NiMo6 component presents improved performance with respect to well defined titania references (parent nanosized anatase or P25) under all illumination conditions tested. The characterization of the solids indicates that the NiMo6 component supported on titania suffers a significant modification of its physico-chemical properties as a function of the loading of the composite system. Such modification appears as a consequence of the interface interaction between the components of the composite system. An electron paramagnetic resonance study of the radical species formed under illumination shows that charge handling through the NiMo6 – TiO2 interface controls the photo-catalytic properties.